Analysis of Receivables Turnover and Inventory Turnover in Measuring the Financial Performance of Perum Bulog - Juhuria; Husriah; Andriani Saputri (International Journal of Multidisciplinary Learners, 2025)
The purpose of this study was to determine the turnover of receivables and inventory turnover in measuring the financial performance of Perum BULOG Baubau Branch Office in accordance with industry standards. The data collection techniques used are observation, documentation, the analysis method used in this research is qualitative. By using the analysis of accounts receivable turnover ratio and inventory turnover ratio. The results of this study indicate that: 1) Based on the receivables turnover ratio, the financial performance of Perum BULOG Baubau Branch Office can be categorised as poor. The drastic decline in sales and significant fluctuations in accounts receivable turnover indicate that the company faces major challenges in maintaining operational stability and credit management efficiency. The overall results of the data analysis indicate that Perum BULOG Baubau Branch Office needs to improve its sales strategy and receivables management to generate better and more stable performance. 2) Based on the inventory turnover ratio, the financial performance of Perum BULOG Baubau Branch Office is unstable in inventory management. The data shows instability in inventory management, in 2020 Perum BULOG had a very high inventory turnover ratio, but other years showed a low turnover ratio. This instability shows that Perum BULOG Baubau Branch Office has difficulty in balancing inventory needs with sales. In 2019, 2022, and 2023, the low inventory turnover ratio indicates that Perum BULOG faces efficiency issues in selling inventory. This could lead to inventory build-up, which impacts storage costs and potential losses due to the decline in value of goods.